Advanced Fibre-Reinforced Polymer (FRP) Composites for Structural Applications 2013
DOI: 10.1533/9780857098641.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the durability of advanced fibre-reinforced polymer (FRP) composites for structural applications

Abstract: Fibre-reinforced polymer (FrP) composites are increasingly being used in the field of civil engineering, either for the rehabilitation/retrofitting of existing infrastructures or for the construction of new structural elements. However, such applications are still recent and there are still unresolved questions regarding the long-term durability of FrP reinforcements or structural elements under service conditions, and their behaviour under accidental fire events as well. In this chapter, it is proposed to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…The HRR is considered the most important parameter to evaluate the growth and spread of fire. 62 The first peak in the HRR curve (pHRR I ) corresponds to the oxidation of the wood with the release of heat. As the burning continues, the protective char layers form and lower the HRR, shown as the valley before the second peak (pHRR II ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRR is considered the most important parameter to evaluate the growth and spread of fire. 62 The first peak in the HRR curve (pHRR I ) corresponds to the oxidation of the wood with the release of heat. As the burning continues, the protective char layers form and lower the HRR, shown as the valley before the second peak (pHRR II ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…TTI is defined as how quick the combustion occurs when the material is subjected to external heat flux. A higher TTI value indicated that longer time was required for the material to reach the pyrolysis temperature 62 and a decreasing fire hazard of a material. 8-30MF and 8-30MF-EN84 specimens had superior TTIs among the modified woods.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The higher impact strength for the recycled PS is caused by a reduction in molecular weight of the polymers due to chain scission, thermal stress, ionizing radiation during different recycling conditions, and chemical ageing of the polymer as a result of oxidative ageing and hydrolytic ageing. The presence of lower molecular weight chains between macromolecules is likely to act as a plasticizer, resulting in increased impact strength [39,53]. However, in the thermo-oxidative degradation of HIPS during lifetime and recycling processes, the polybutadiene phase undergoes chemical changes that result in the polymer's mechanical failure [54].…”
Section: Toughnessmentioning
confidence: 99%
“…Nowadays, composites reinforced with synthetics fibers such as carbon or glass fibers (CFRP or GFRP) are commonly used in various industrial fields from automotive to aerospace in order to reduce the weight of the final pieces [1].…”
Section: Introductionmentioning
confidence: 99%